1961
DOI: 10.1152/ajplegacy.1961.201.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial creatine phosphate and nucleotides in anoxic cardiac arrest and recovery

Abstract: In isolated perfused dog hearts, myocardial concentrations of creatine phosphate (CrP) and adenosine triphosphate (ATP) decreased following a 45-min period of anoxia. After partial resuscitation by perfusion of oxygenated blood for 30 min, CrP had risen again to approximately control values but ATP concentration had fallen lower. Increased concentrations of deaminated derivatives of ATP, chiefly inosine, were found in the myocardium and in the perfusion effluent after anoxia. The myocardial inosine was still e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

1965
1965
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(14 citation statements)
references
References 0 publications
3
10
1
Order By: Relevance
“…The values obtained for Pi served as rough indicators of phosphate bond hydrolysis. The levels of Pi found in the arrested hearts were higher than those found in biopsy samples frozen in situ (26), but were equivalent to those found in conventional biopsy samples or in perfused, ar-213 rested hearts (27,44,45). Among the arrested normal and hypertrophied hearts, the values for CrP in the left ventricles equaled those previously reported (27,44), and the values for the right ventricles were higher.…”
Section: Discussionsupporting
confidence: 64%
“…The values obtained for Pi served as rough indicators of phosphate bond hydrolysis. The levels of Pi found in the arrested hearts were higher than those found in biopsy samples frozen in situ (26), but were equivalent to those found in conventional biopsy samples or in perfused, ar-213 rested hearts (27,44,45). Among the arrested normal and hypertrophied hearts, the values for CrP in the left ventricles equaled those previously reported (27,44), and the values for the right ventricles were higher.…”
Section: Discussionsupporting
confidence: 64%
“…Various explanations were proposed, including dysfunction of mitochondria, and lactic acid and pH changes influencing ATP synthesising enzyme kinetics. However, one observation suggested that the basis of this prolonged post anoxic/ischemic ATP depletion was via the loss of ATP precursors from the heart and into the perfusate or blood stream [38] (similar observations were being made by Robert Berne around the same time [39]). The importance of this loss of precursors, which also occurs in man [40], stems from the fact that the heart predominately utilises the purine salvage pathway (Fig.…”
Section: Basis For Atp Depletionmentioning
confidence: 77%
“…4. The 30-min time course demonstrates a typical sequence of high-energy phosphate depletion during cardiac arrest (29,30). As phosphocreatine decreases over the first 10 min to an undetectable concentration, Pi concentration increases while ATP concentration remains the same.…”
Section: Resultsmentioning
confidence: 98%